(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Introduction: PCOS is a very common disorder of reproductive women characterized by hyperandrogenism and chronic auovulation. The beneficial effects on micronutrients supplements may have been mediated not only through the presence of multiple vitamin & minerals and multiple antioxidant such as vitamin C and vitamin E. It also mediated insulin sensitization with inositol and improvement of the blood flow in the pelvic organ with the presence of L-arginine. Multiple micronutrients supplementation is a cost effective remedy that is well tolerated with no adverse effects. Its use as an adjuvant in fertility treatment may benefit women pre conceptionaly. Objective: The aims of this study was to investigate the effects of MMN in subfertile women with PCOS.And also to demonstrate that MMN is act as adjuvant therapy to a standard ovulation induction regimen. And to identify ovulation rate and pregnancy rate. Materials and methods: This is a prospective randomized control trial. In this study total 100 patients between the age of 20-40 years were taken from infertility OPD, BSMMU and in private sector, Baridhara, Dhaka, during the period from July 2011 to June 2012.Among 100 patients 50 infertile patients undergoing ovulation induction for 3 months were allocated to receive adjuvant MMN treated as group A. 50 infertile patient undergoing ovulation induction were not allocated to receive adjuvant treated as group B. Results: Clinical pregnancy rate are assessed after third cycle or as soon as the women achieved pregnancy. There was no significant differences in age, menstrual history, BMI (kg/m2) in both groups. This difference was statistically significant p<0.04. And also shows the endometrial thickness with TVS >9mm in 31 patients and less than 9mm in 11 patients with case group compared with the control group >9mm 11 patient and <9mm in 17 patients which is statistically significant p value <0.05. There was no significant difference in progesterone in both groups. There were 22 of 50 patient conceived during the study 2 miscarriage in first trimester in group A and 6 of 50 are conceived in group B and 2 miscarriage in 1st trimester. There was significant difference pregnancy rate p <0.001. Discussion: Our study is to demonstrate that multiple micronutrients supplementation is adjuvant therapy to a standard ovulation induction regimen in women undergoing treatment for anovulatory PCOS patients. The effect of this adjuvant therapy is improved the ovulation and pregnancy rate. Women who take adjuvant micronutrients supplementation during ovulation induction have a higher chance of pregnancy compared with women without micronutrients supplementation. Conclusions: Women who take adjuvant micronutrients supplementation during ovulation induction have a higher chance of pregnancy compared with women without micronutrients supplementation. J. Paediatr. Surg. Bangladesh 4(2): 50-53, 2013 (July)